The Influence of Financial Performance and Company Size on Company Value with Good Corporate Governance as a Moderating Variable - Wulan Ndatika, Utyea; Purwidianti, Wida; Tubastuvi, Naelati; Alfalisyado (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine the effect of financial performance and company size on company value with Good Corporate Governance as a moderating variable in the consumer goods industry sector in 2019-2021. The population in this study was 72 companies in the consumer goods industry sector, with a research sample of 24 companies. This type of research is a quantitative method. With the purposive sampling method, the data used is secondary data. The data analysis technique uses SPSS 26. The results of the analysis obtained are that Financial Performance has a negative and significant effect on Company Value, Company Size does not affect company value, Good Corporate Governance can moderate the relationship between the influence of Financial Performance on Company Value, Good corporate governance can moderate relationship between company size and company value.